69.6k views
0 votes
Plz help me with this

Plz help me with this-example-1
User Daxim
by
5.2k points

2 Answers

5 votes

Answer:

10x^3 - 34x^2 + 33x - 7

Explanation:

Multiply each term of the trinomial by each term of the binomial. Then combine like terms.

(2x^2 - 4x + 1)(5x - 7) =

= 10x^3 - 14x^2 - 20x^2 + 28x + 5x - 7

= 10x^3 - 34x^2 + 33x - 7

User Artworkjpm
by
5.0k points
2 votes

Answer: 10x³ -34x² +33x - 7

Explanation:

(2x² - 4x + 1)(5x - 7)

= (5x - 7)(2x² - 4x + 1)

= 5x(2x² - 4x + 1) -7(2x² - 4x + 1)

= 10x³ - 20x² + 5x

+ -14x² + 28x - 7

= 10x³ - 34x² + 33x - 7

User Mr Singh
by
5.6k points